Angling‐Induced Impacts on Recruitment and Contributions to Reproduction in Florida Bass. Issue 5 (5th July 2017) - Trippel, Nicholas A.; Hargrove, John S.; Leone, Erin H.; Austin, James D.; Allen, Micheal S.
Abstract: Black basses Micropterus spp. are the focus of extensive management efforts throughout North America, where they support a multibillion‐dollar recreational sport fishery. Harvest rates in many bass fisheries have declined in recent decades, yet a growing number of studies have proposed that catch‐and‐release angling practices, such as bed‐fishing in which anglers intentionally target bass while the fish are defending their nests, can decrease individual reproductive success. In response, management agencies have restricted fishing during the spawning period in some regions. We evaluated the impacts of catch‐and‐release bed‐fishing on Florida Bass M. salmoides floridanus nest success, reproductive success, production of fall recruits, and the number of parents that contributed to reproduction. Eighteen replicate populations simulating natural Florida lakes were established, and ponds were assigned either a bed‐fishing ( n = 10) or a control treatment ( n = 8). Snorkel surveys were conducted throughout the spawning period to track nest formation and nesting success rates, and 10 months after establishment all ponds were drained, recruits counted, and fin clips collected for genetic parentage analysis. A series of candidate generalized linear mixed models were compared using Akaike's information criterion and likelihood ratio tests to assess the relative importance of fishing treatment and year, along with other relevant variables in predicting nest success, recruitment, and reproductive success. We observed significant reductions in nest success rates ( z = −2.13, P = 0.03) but not recruitment levels ( z = −1.31, P = 0.19), in populations that were bed fished relative to control ponds. Capture history poorly predicted individual reproductive success and the number of adults that contributed to fall recruitment did not differ by treatment (χ 2 = 0.06, P = 0.81). Results from this study indicated that bed‐fishing practices may have some impacts on individual nest success but did not influence recruitment or overall reproductive success of Florida Bass at the population level. Received October 5, 2016; accepted February 28, 2017 Published online July 5, 2017